Lipoplexes carrying mRNA encoding Gag protein modulate dendritic cells to stimulate HIV-specific immune responses. (January 2013) - De Haes, Winni; Rejman, Joanna; Pollard, Charlotte; Merlin, Céline; Vekemans, Marc; Florence, Eric; De Smedt, Stefaan C; Grooten, Johan; Vanham, Guido; De Koker, Stefaan; Van Gulck, Ellen
Aim: Cationic lipids (Lipofectamine™ [Invitrogen, Merelbeke, Belgium] and 1, 2-dioleoyl-3-trimethylammonium-propane/1, 2-dioleoyl- sn -glycero-3-phosphoethanolamine) and polymers (jetPEI™ and in vivo -jetPEI™ [Polyplus-transfection, Illkirch, France]) were evaluated for their potential to deliver mRNA to monocyte-derived dendritic cells.Materials & methods: Lipoplexes and polyplexes, containing mRNA encoding GFP or Gag protein, were incubated with human monocyte-derived dendritic cells and transfection efficiencies were assessed by flow cytometry.Results: Lipofectamine was by far the most efficient in mRNA delivery, therefore it was used in further experiments. Incubation of monocyte-derived dendritic cells isolated from HIV-1-positive donors with mRNA encoding Gag protein complexed to Lipofectamine resulted in 50% transfection. Importantly, coculture of these Gag-transfected dendritic cells with autologous T cells induced an over tenfold expansion of IFN-γ- and IL-2-secreting CD4 + and CD8 + T cells.Conclusion: Cationic lipid-mediated mRNA delivery may be a useful tool for therapeutic vaccination against HIV-1. This approach can be applied to develop vaccination strategies for other infectious diseases and cancer. Original submitted 26 January 2012; Revised submitted 17 April 2012; Published online 14 August 2012